Determining the Type of Clothing Suitable for Women With An Non Typical Figure - Abdurakhimova Manzura Sadiqovna (Zien Journals, 2022)
In this article, the results of the analysis of the types of clothing, colours and styles suitable for women with atypical body shapes, as well as their compatibility with modern fashion, are highlighted based on the analysis of the test questionnaire.
Keywords: questionnaire; analysis; dress; desire